EFL Students’ Motivational Regulation and Behavioral Engagement in Academic Reading Tasks: A Mixed-Methods Inquiry - Nila Kencana; Sinarman Jaya (IJECA (International Journal of Education and Curriculum Application), 2026)
Motivational regulation and behavioral engagement influence academic reading in EFL higher education, yet many students struggle to stay motivated and actively involved in demanding tasks. Prior research has often treated these constructs separately and relied on self-report data, so we still know little about how students regulate their motivation in practice or how this connects to their observable engagement. This study aims to examine how motivational regulation relates to behavioral engagement in EFL academic reading. It also aims to identify the strategies students use to regulate motivation and sustain engagement during cognitively demanding reading tasks through a mixed-methods approach. The participants were 114 third-semester EFL students from four universities in Bengkulu, Indonesia, selected through purposive sampling based on their enrollment in academic reading courses. Quantitative data were collected through a motivational regulation and engagement questionnaire and analyzed using descriptive statistics and correlation analysis to identify patterns and relationships between constructs. Qualitative data were obtained through semi-structured interviews and analyzed thematically to explain the quantitative results. The findings indicate that students demonstrated relatively high behavioral engagement in academic reading (M = 3.17). Students also reported strong goal-directed motivation (M = 3.33) and self-regulation (M = 3.10–3.25). Qualitative evidence suggests that students who actively regulate their motivation are more likely to continue reading difficult texts and complete their tasks. Interview results further revealed that goal setting, effort regulation, and perceived task value supported sustained engagement in reading activities. These findings highlight motivational regulation as a key mechanism supporting behavioral engagement in EFL academic reading. The study contributes empirical evidence showing how goal setting, time management, and comprehension monitoring support sustained engagement during demanding reading tasks. Pedagogically, the findings suggest that academic reading instruction should explicitly integrate motivational regulation strategies through structured pre-reading goals, guided monitoring activities, and reflective tasks to help students sustain effort and engagement in higher education EFL contexts.